Ne zhdite meni︠a︡ v Monte-Karlo - Kulikova, Galina (Neserʹeznyĭ detektiv, 2021)
"Who doesn't want to take a trip on a giant cruise ship! But what if you didn't come to it of your own free will? And must play someone else's role to hide from a brutal killer? Writing another report for her magazine, Veronika Ivleva got lost in a dense forest. From that moment on, her life quickly rushed from one adventure to another. At the wedding of her best friend, she was treated to sleeping pills and loaded onto a motor ship sailing along the Volga. Trying to find out who set it all up and why, Veronica suddenly found herself on the verge of death - a stranger tried to kill her. To stay alive, the girl had to flee. Veronica decided that no one would find her on a cruise ship in the Mediterranean. Oh, how wrong she was!" --